2020
DOI: 10.1186/s12879-020-4941-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing congenital Cytomegalovirus infection: don’t get rid of dried blood spots

Abstract: Background: Congenital Cytomegalovirus (cCMV) is a serious global public health issue that can cause irreversible fetal and neonatal congenital defects in symptomatic or asymptomatic newborns at birth. In absence of universal cCMV screening, the retrospective diagnosis of cCMV infection in children is only possible by examining Dried Blood Spot (DBS) samples routinely collected at birth and stored for different time spans depending on the newborn screening regulations in force in different countries. In this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
(48 reference statements)
0
25
0
Order By: Relevance
“… 17 Therefore, screening studies based on CMV polymerase chain reaction of dried blood spots will probably underestimate cCMV prevalence, but with improved methods, this form of testing may become more useful. 49 , 104 To assess possible differences in the estimates due to the biological specimens used for screening for cCMV, we conducted subgroup analysis comparing studies that carried out screening using urine and/or saliva samples with those that used only blood or serum. There was a significant difference in the cCMV prevalence rates between the biological specimens used for screening: 0.79% (95% CI, 0.63%-1.00%) for urine or saliva vs 0.31% (95% CI, 0.22%- 0.46%) for blood or serum only ( P < .001 for subgroup differences) (eFigure 3 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“… 17 Therefore, screening studies based on CMV polymerase chain reaction of dried blood spots will probably underestimate cCMV prevalence, but with improved methods, this form of testing may become more useful. 49 , 104 To assess possible differences in the estimates due to the biological specimens used for screening for cCMV, we conducted subgroup analysis comparing studies that carried out screening using urine and/or saliva samples with those that used only blood or serum. There was a significant difference in the cCMV prevalence rates between the biological specimens used for screening: 0.79% (95% CI, 0.63%-1.00%) for urine or saliva vs 0.31% (95% CI, 0.22%- 0.46%) for blood or serum only ( P < .001 for subgroup differences) (eFigure 3 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite all of this, some authors provided evidence of the high sensitivity of DBS for the retrospective diagnosis of cCMV in children developing neurological sequelae in the first few years of life. Moreover, it is clear that some serious health problems (such as SNHL, cortical development, pachygyria, cholestasis) would have been lessened as a result of DBS retrospective diagnosis [ 71 , 72 ]. Finally, some authors reported the usefulness of DBS to identify children at risk of developing long-term sequelae [ 73 , 74 ].…”
Section: Neonatal Screening and Diagnosismentioning
confidence: 99%
“…In some countries, dried blood spots (DBS) taken in the first week of life for newborn screening are stored and used for retrospective diagnosis of congenital CMV infection even if the baby presents after the perinatal period. 5 However, long-term DBS storage and virological diagnosis from DBS are not feasible in all settings.…”
Section: Discussionmentioning
confidence: 99%